Late‐Stage 18O Labeling of Primary Sulfonamides via a Degradation–Reconstruction Pathway. Issue 19 (5th March 2020) - Reilly, Sean W.; Bennett, Frank; Fier, Patrick S.; Ren, Sumei; Strotman, Neil A.
Abstract: A late‐stage 18 O labeling approach of sulfonamides that employs the corresponding unlabeled molecule as the starting material was developed. Upon deamination of the sulfonamide, a sulfinate intermediate was isotopically enriched using eco‐friendly reagents H2 18 O and 15 NH3 (aq) to afford a M+5 isotopologue of the parent compound. This degradation–reconstruction approach afforded isolated yields of up to 96 % for the stable isotope labeled (SIL) sulfonamides, and was compatible with multiple marketed therapeutics, including celecoxib, on a gram scale. The SIL products also exhibited no 18 O/ 16 O back exchange under extreme conditions, further validating the utility of this green strategy for drug labeling for both in vitro and in vivo use. This procedure was also adapted to include pharmaceutically relevant methyl sulfones by using 13 CH3, affording M+5 isotopic enrichment, thereby illustrating the broad utility of this methodology. Abstract : A late‐stage 18 O labeling approach of sulfonamides that employs the corresponding unlabeled molecule as the starting material was developed. Upon deamination of the sulfonamide, a sulfinate intermediate was isotopically enriched using eco‐friendly reagents H2 18 O and 15 NH3 (aq) to afford a M+5 isotopologue of the parent compound.